(3Gdadc GdSGFQ aj CfSGH GdbHGFd hGdYTGFQs - (3GdcGXej GdCYQLj, LYaQ Hf eMeO Hf LYaQ, J (B1332 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg (B... (3deG cGf Gdedc GdeWdY hGdhGdj GdhGLH GdGJHGY UGMH aVjdJj GdSja hGdbde hGdj hdGI GdYQH hGdYLe GdPj hbY Ydi MSf SjQJg GdGJaGb hWGQ fSQ UjJg HeMGSf GdChUGa (B...s
(3BNQgG (B:s
... (3hhgf GdYXe efj adG CSJWHY HYO Pdc GdHGOjI hbO ZQeJ Ydi Gf CScf OGQ GdOhdI hdjSJ dfG OGQ Jchf ddYdhjGJ eMd GSJbQGQ aGdeCehd ef aVdc Cf JLhO HPdc hdc YfO Gddg ef GdLRA CaVdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\129s
(3eYLe GdeDdajf (B1\495s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs